Pandangan Ibn al-Haytham Tentang Jiwa - Usep Mohamad Ishaq (Psikis : Jurnal Psikologi Islami, 2021)
Ibn al-Haytham (965-1039) is hitherto known merely as a prominent scientist and mathematician who contributed to the development of science and mathematics. His contribution in philosophy and religious sciences are not exposed yet, therefore some scholars e.g. Muhammad Saud (1990), Saleh Beshara Omar (1977), Roshdi Rashed (2007), and many others, consider him neglecting philosophical and religious issues and regarded him to be a secular-positivist scholar. consider him to be uninterested in philosophical and religious issues. However, study has been done from the his primary works, especially his work namely Kitab Thamarah al-Ḥikmah that still rarely studied by researchers of Ibn al-Haytham thought. The method used in this study is the historical and philosophical methods. The results obtained clearly show that Ibn al-Haytham was not merely scientist and mathematician, he was also a philosopher who had contributed in explaining human psychology which accepted other philosophers. He elucidates the faculties of human soul and explains the relation between soul and the concept of happiness.